Tropical cyclones of the North Atlantic Ocean, 1871-1980 - Neumann, Charles J.; Environmental Research Laboratories (U.S.); National Hurricane Research Laboratory.; National Hurricane Center (1965-1995); National Climatic Center. ([Boulder, Colo.?] : U.S. Dept. of Commerce, National Oceanic and Atmospheric Administration, National Weather Service, Environmental Data and Information Service, Environmental Research Laboratories, 1981)
Mode of access: Internet.